Impact of Soybean Bioactive Peptides on Growth, Lipid Metabolism, Antioxidant Ability, Molecular Responses, and Gut Microbiota of Oriental River Prawn (Macrobrachium nipponense) Fed with a Low-Fishmeal Diet - Chang Yang; Bo Liu; Liangkun Pan; Dong Xia; Cunxin Sun; Xiaochuan Zheng; Peng Chen; He Hu; Qunlan Zhou (Biology)
The substitution of fishmeal with high-level soybean meal in the diet of crustaceans usually induces lipid accumulation and oxidative stress in the hepatopancreas. Therefore, it is essential to alleviate these adverse effects. In the present study, SBPs were used to alleviate the negative effects of a fishmeal decrease on the growth performance, lipid metabolism, antioxidant capacity, and gut microbiota of oriental river prawn (Macrobrachium nipponense) in an 8-week feeding trial. Three isonitrogenic and isolipidic diets were prepared as follows: R (reference diet with 32% fishmeal), CT (control diet with 22% fishmeal), and SBP (22% fishmeal with 1.25 g/kg soybean bioactive peptides). The prawns (initial biomass per tank 17 g) were randomly divided into three groups with four replicates. The results showed that the low-fishmeal diet induced the following: (1) the inhibition of growth performance and survival of prawns; (2) an increase in triglyceride content in the hepatopancreas and hemolymph and downregulation of carnitine palmitoyl transferase 1 (cpt1) gene expression; (3) a reduction in antioxidant enzymes’ activities and their genes expression levels and an increase malondialdehyde (MDA) content; and (4) an increase in the abundance of the conditional pathogen Pseudomonas in the gut. SBPs supplementation in the CT diet effectively alleviated most of the above adverse effects. SBPs enhanced inducible nitric oxide synthase (iNOS) activity to synthesize nitric oxide (NO) by activating the imd-relish pathway. Most importantly, SBPs increased the potential probiotic Rikenellaceae_RC9_gut_group abundance and decreased the abundance of the conditional pathogen Pseudomonas in the gut. In conclusion, SBPs supplementation can improve low-fishmeal-diet-induced growth inhibition by regulating the gut microbiota composition to ameliorate lipid deposition and oxidative stress and strengthen immune status in oriental river prawn.